Hypoxia promotes the proliferation of mouse liver sinusoidal endothelial cells: miRNA–mRNA expression analysis. Issue 1 (1st January 2021) - Qing, Zhe; Huang, Hanfei; Luo, Qun; Lin, Jie; Yang, Shikun; Liu, Tao; Zeng, Zhong; Ming, Tingfeng
ABSTRACT: During the initial stage of liver regeneration (LR), hepatocytes and liver sinusoidal endothelial cells (LSECs) initiate regeneration in a hypoxic environment. However, the role of LSECs in liver regeneration in hypoxic environments and their specific molecular mechanism is unknown. Therefore, this study aimed to explore the miRNA–mRNA network that regulates the proliferation of LSECs during hypoxia. In this study, first, we found that the proliferation ability of primary LSECs treated with hypoxia was enhanced compared with the control group, and then whole transcriptome sequencing was performed to screen 1837 differentially expressed (DE) genes and 17 DE miRNAs. Subsequently, the bioinformatics method was used to predict the target genes of miRNAs, and 309 pairs of interacting miRNA–mRNA pairs were obtained. Furthermore, the miRNA-gene action network was established using the negative interacting miRNA–mRNA pairs. The selected mRNAs were analyzed by Gene Ontology (GO) enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, and biological processes (BP) and signal pathways related to LSEC proliferation that were significantly enriched in GO-BP and KEGG were selected. Finally, 22 DE genes and 17 DE miRNAs were screened and the network was created. We also successfully verified the significant changes in the top six genes and miRNAs using qRT-PCR, and the results were consistent with the sequencing results. This study proposed that a specific miRNA–mRNA network is associated with hypoxia-induced proliferation of LSECs, which will assist in elucidating the potential mechanisms involved in hypoxia-promoting liver regeneration during LR.